Climate-Related Vulnerability and Risk Assessment of Main Ocean Uses: An Overview - Fernandes, Miguel; Vieira da Silva, Carina; Frazão Santos, Catarina (Frontiers in Marine Science, 2022)
Vulnerability and risk analyses have been increasingly used in a wide variety of contexts to support ocean management and planning processes. Depending on the context, such analyses may focus on different dimensions, spatial scales, and hazards. In the particular context of climate change, the variability inherent to the developed assessments has led to the emergence of numerous methodological frameworks, allowing for advances in the field while raising uncertainties on applied concepts and approaches. In the present study, we developed a systematic literature review to analyze and discuss the key concepts, methodologies, and limitations of existing vulnerability and risk assessments of main ocean uses to climate change. We analyzed over 314 scientific references regarding the elements considered in the analysis, dimensions, type of indicators, maritime activities, climate-related drivers of change, and spatial scales. Results show that most vulnerability and risk assessments address fisheries and marine conservation, and that sea-level rise and extreme events are the most frequently considered climate-related drivers of change. The main identified limitations pertain to the level of subjectivity and the tremendous variety of concepts, areas of expertise, and systems addressed in such studies. We highlight that further research is needed particularly on the development of cross-sectoral studies and integrative approaches. There is also a need for assessments explicitly designed to support ocean planning and integrated marine management processes. Review processes such as the present one provide a “big picture”, allowing for a global view on complex topics, and contributing to advances in the field.